ANALISIS SISTEM PENDUKUNG KEPUTUSAN DALAM PEMILIHAN PROGRAM STUDI DI AMIK DAN STIKOM TUNAS BANGSA PEMATANGSIANTAR DENGAN METODE MOORA - Apriliani, Lulu; Solikhun, Solikhun; Lubis, Muhammad Ridwan; Saputra, Widodo (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
The many choice of study programs in University, the fact is that it does not make prospective students quickly and easily decide the study program they will take. The selection of study programs is one of the problems faced by students who want to continue their studies to Universities. Many student feel confused about what study program is suitable for them. There are many factors that cause this, including because of the desire of parents, the ability of  yourself, ideals,prospect, or it could be just to follow along with other friends. In this paper the author uses the Moora Method as the weighting method used.  Keywords: SPK, MOORA, Selection of Study Program  The many choice of study programs in University, the fact is that it does not make prospective students quickly and easily decide the study program they will take. The selection of study programs is one of the problems faced by students who want to continue their studies to Universities. Many student feel confused about what study program is suitable for them. There are many factors that cause this, including because of the desire of parents, the ability of  yourself, ideals,prospect, or it could be just to follow along with other friends. In this paper the author uses the Moora Method as the weighting method used. Keywords: SPK, MOORA, Selection of Study Program